(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Differentiation is a way of planning the teaching methods and materials in which teachers proactively adapt instructional activities, teaching processes and curricular resources in order to address the various students’ needs. There are three major principles which acts as a foundation behind differentiated instruction. They are ongoing assessments, flexible grouping and respectful tasks. A differentiated teacher plans and prepares the instructions and teaching based on individual students, not on a pre-planned fixed curriculum. Teaching Biology using the conventional methods about Animal kingdom, and Nutrition and Health is challenging because the scientific terms are difficult to understand as the contents are descriptive in nature. The anatomical and morphological terms are very hard for the students to comprehend. Students with varied abilities scored poorly in Biology due to monotony of conventional methods. Hence the present study was undertaken with the objective to find out the effectiveness of Differentiated Instruction (DI) in learning Biology. In this study the Differentiated Instruction (DI) modules were designed using a set of teaching aids, assignments and activities for the selected chapters from class 9 of NCERT book. An experimental research was conducted with sixty (N=60) students of a Government Higher Secondary School. The students were tested using a Pre-test of Twenty-five questions on Animal Kingdom, and Nutrition and health. An intervention based on Differentiated Instruction was given to the Experimental group for eight weeks of 40 instructional classes. The effectiveness of DI was measured by giving post-test. The data was analyzed and examined using SPSS trial version and the statistical analysis involved (a) descriptive statistics, (b) Paired sample t -test to find out the mean scores of the same topics (prior and after the intervention). The results indicate that there was significant improvement in learning Biology as a result of Differentiated Instruction. So it is recommended that Differentiated Instruction is highly beneficial to the students for teaching Biology at secondary level.